2021
DOI: 10.1002/pat.5505
|View full text |Cite
|
Sign up to set email alerts
|

Construction of crosslinking network structures by addingZnOandADRin intumescent flame retardantPLAcomposites

Abstract: Different proportion of nano zinc oxide (nano ZnO) and chain extender (ADR) were combined with the intumescent flame retardant and then added into the PLA matrix. The thermal stability, flame retardant performance, and mechanical properties were studied. The gel content results showed that crosslinking structures were obtained after the addition of nano ZnO and ADR, which were generated by the catalytic chain scission effect of nano ZnO and chain extension effect of ADR. With addition of 1% nano ZnO and 1.6% A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…The mechanical properties test results showed that when DCP and TAIC were added at the same time, the mechanical properties improved significantly and were close to that of pure PLA. Compared with the ADR/nano ZnO system [51], the mechanical properties of the two system are similar to those of pure PLA, which means that both crosslinked structures can achieve excellent performance. In addition, the study of Zhang [54] showed that the mechanical properties of PLA composites decreased significantly after the addition of flame retardants.…”
Section: The Mechanical Properties Of Pla and Its Compositesmentioning
confidence: 97%
See 1 more Smart Citation
“…The mechanical properties test results showed that when DCP and TAIC were added at the same time, the mechanical properties improved significantly and were close to that of pure PLA. Compared with the ADR/nano ZnO system [51], the mechanical properties of the two system are similar to those of pure PLA, which means that both crosslinked structures can achieve excellent performance. In addition, the study of Zhang [54] showed that the mechanical properties of PLA composites decreased significantly after the addition of flame retardants.…”
Section: The Mechanical Properties Of Pla and Its Compositesmentioning
confidence: 97%
“…It was found that the addition of ADR and nano ZnO could balance the mechanical properties and the flame retardant performance of the flame-retardant PLA. We tried to add different synergists to PLA [51,52]. However, nano ZnO is not recommended to be used in biodegradable plastic PLA because it is toxic to organisms.…”
Section: Introductionmentioning
confidence: 99%
“…A vacant aluminum pan was applied as the reference. The crystallinity (χ c ) was calculated by the below formula 1 13,19,22,23,26 :…”
Section: Differential Scanning Calorimetry Analysismentioning
confidence: 99%
“…In a general sense, it is hard for a pristine polyester to meet all requirements of practical applications 3,18 and commonly the desired properties are given by melt blending with other functional fillers 5,[19][20][21][22] or reacting with some active materials, 21,23 making up the respective weakness. With regards to PLA, a large number of studies on improving its properties by various means have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation